Co-pyrolysis of binary and ternary mixtures of microalgae, wood and waste tires through TGA. (November 2019) - Azizi, Kolsoom; Moshfegh Haghighi, Ali; Keshavarz Moraveji, Mostafa; Olazar, Martin; Lopez, Gartzen
Abstract: Degradation behavior and kinetics of microalgae chlorella vulgaris, wood, scrap tire and binary and ternary mixtures were investigated by using thermogravimetry analysis method. Experiments were carried out at different heating rates of 10 − 20 and 40 ° C / min from ambient temperature to 600 °C. The results showed that decomposition of microalgae, wood and tire take place in three stages and the second stage is the main thermal decomposition step. Besides, heating rate enhancements shift the maximum peak temperature of microalgae, wood and scrap tire from 300 °C, 350 °C and 380 °C to 340 °C, 390 °C and 420 °C, respectively. In the case of the ternary mixture, the maximum peak temperature of the mixture was approximately equal to the maximum peak temperature of the tire. The interaction between materials was studied and the results showed that the interaction is inhibitive rather than synergistic. The results of kinetic investigation showed that the tire and the wood have the highest (273.64 kJ/mol) and the lowest (120.96 kJ/mol) activation energy, respectively. The presence of wood and microalgae increased the total weight loss of binary mixture of microalgae-tire and wood-tire, while tire presence did not improve the degradation of microalgae-wood mixture. Highlights: Co-pyrolysis of binary and ternary mixtures of different biomass was investigated. Wood presence improved the pyrolysis of microalgae-tire mixture. Microalgae presence improved the pyrolysis of wood-tire mixture. Tire presence did not improve the degradation of microalgae-wood mixture. Maximum peak temperature of ternary mixture was almost equal to that of tire.